Zeitgenössische Russische Kunst. - Cullerne Bown, Matthew (Oxford : Phaidon Press Limited Oxford, 1989)
Albert, Jurij ; Bruskin, Grisha ; Bulatow, Erik ; Bulgakowa, Olga ; Dybski, Ewgeni ; Faibisowitsch, Simen ; Filippow, Andrej ; Filippowa, Katja ; Ganikowsky, Igor ; Infante, Francisco ; Iwanow, Viktor ; Jankilevskij, Vladimir ; Kabakov, Ilya ; Kantor, Maksim ; Kisewalter, Georgi ; Kopystianskaya, Svetlana ; Kopystiansky, Igor ; Korolew, Juri ; Kulinitsch, Anatoli ; Lawrowa, Irina ; Lubennikov, Ivan ; Makarewitsch, Igor ; Miljukow, Boris ; Mironenko, Sergej ; Mitta, Evgeny ; Moisejenko, Ewsei ; Mylnikov, André ; Nachova, Irina ; Nasarenko, Tatjana ; Nesterova, Natalija ; Orlow, Boris ; Owtschinnikow, Nikolai ; Petrow, Arkadij ; Prigow, Dmitrij ; Prisekin, Sergej ; Ptschelnikow, Igor ; Roiter, Andrej ; Sacharow, Wadim ; Salachow, Tair ; Salachowa, Aidan ; Satulowskaja, Irina ; Schilinski, Dmitri ; Schutow, Sergej ; Schwarzman, Michail ; Slepysev, Anatolij ; Smertin, Boris ; Steinberg, Edvard ; Sundukow, Aleksej ; Tabenkin, Ilja ; Tabenkin, Lew ; Tschujkow, Iwan ; Turnova, Natalia ; Wasiljew, Oleg ; Winogradow, German ; Wolkow, Andrej Viktorowitsch ; Wolkow, Sergej ; Zykalow, Dmitri
Biog., tent., bibliog. p.121-125
Duits
boek
Keywords: Sovjet-Unie; Rusland